2003
DOI: 10.1155/2003/278152
|View full text |Cite
|
Sign up to set email alerts
|

Development of Proteomic Patterns for Detecting Lung Cancer

Abstract: Lung cancer is at present the number one cause of cancer death and no biomarker is available to detect early lung cancer in serum samples so far. The objective of this study is to find specific biomarkers for detection of lung cancer using Surface Enhanced Laser Desorption/Ionization (SELDI) technology. In this study, serum samples from 30 lung cancer patients and 51 age-and sex-matched healthy were analyzed by SELDI based ProteinChip reader, PBSII-C. The spectra were generated on WCX2 chips and protein peaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 13 publications
0
45
0
1
Order By: Relevance
“…Unlike gene expression studies of tumor tissues, autoantibody profiling is done in serum, which can be much less invasively obtained and is easily monitored over time. Likewise, whereas there has been intensive activity in the use of proteomic approaches to identify biomarkers in sera (15), monitoring the immune response takes advantage of the inherent biological amplification provided by autoantibodies which can be more easily detected than low abundant proteins in a complex biological milieu, such as serum. Whereas our study suggests that the humoral immune response may be useful in the diagnosis and classification of tumors, it will also be important to investigate the role of these autoantibodies in promoting tumor development, especially in light of the growing evidence linking inflammation and cancer (24,25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike gene expression studies of tumor tissues, autoantibody profiling is done in serum, which can be much less invasively obtained and is easily monitored over time. Likewise, whereas there has been intensive activity in the use of proteomic approaches to identify biomarkers in sera (15), monitoring the immune response takes advantage of the inherent biological amplification provided by autoantibodies which can be more easily detected than low abundant proteins in a complex biological milieu, such as serum. Whereas our study suggests that the humoral immune response may be useful in the diagnosis and classification of tumors, it will also be important to investigate the role of these autoantibodies in promoting tumor development, especially in light of the growing evidence linking inflammation and cancer (24,25).…”
Section: Resultsmentioning
confidence: 99%
“…Several groups are using proteomic approaches using serum to identify biomarkers for the early detection of lung cancer (11)(12)(13)(14). This is a daunting challenge, as this requires identification of relatively low abundant proteins in a complex mixture of highly abundant serum proteins, such as albumin (15).…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratories have demonstrated the feasibility of using mass spectrometric proteomic pattern analysis for the diagnosis of several categories of tumors, including ovarian, breast, lung, pancreas, and prostate cancer (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). In one of the earliest contributions, investigators from Eastern Virginia Medical School (EVMS) 10 and the Fred Hutchison Cancer Research Center (FHCRC) demonstrated that surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF-MS) protein profiles may have clinical utility as a diagnostic tool for the early detection of prostate cancer, including prostatic adenocarcinoma (PCa) (6,8 ).…”
Section: © 2005 American Association For Clinical Chemistrymentioning
confidence: 99%
“…In oncology the method has been used for tumor classification, evaluation of biomarkers [19][20][21][22][23]. The sample size represents a limitation in our study, but the method used is a potentially powerful tool for investigating multilevel interactions [24].…”
Section: Discussionmentioning
confidence: 99%